Combined Pan‐HER and ALK/ROS1/MET Inhibition with Dacomitinib and Crizotinib in Advanced Non–Small Cell Lung Cancer: Results of a Phase I Study. Issue 5 (May 2016) - Jänne, Pasi A.; Shaw, Alice T.; Camidge, Ross D.; Giaccone, Giuseppe; Shreeve, Martin S.; Tang, Yiyun; Goldberg, Zelanna; Martini, Jean‐François; Xu, Huiping; James, Leonard P.; Solomon, Benjamin J.
ABSTRACT : Introduction: : This phase I study investigated the activity of the irreversible pan‐human epidermal growth factor receptor inhibitor dacomitinib in combination with the mesenchymal‐epithelial transition factor/anaplastic lymphoma kinase/ROS proto‐oncogene 1, receptor tyrosine kinase inhibitor crizotinib in advanced non–small cell lung cancer. Methods: : Patients with progression after at least one line of chemotherapy or targeted therapy received dacomitinib once daily and crizotinib once daily or twice daily, with doses escalated until intolerable toxicity; the expansion cohorts received the maximum tolerated dose of the combination. The primary objective was to define the recommended phase II dose; secondary objectives included assessment of safety and activity of the combination in epidermal growth factor receptor inhibitor‐resistant patients and correlation with tumor biomarkers. Results: : Seventy patients were treated in the dose‐escalation (n = 33) and expansion phases (n = 37), with the maximum tolerated dose defined as dacomitinib, 30 mg once daily, plus crizotinib, 200 mg twice daily. Grade 3 or 4 treatment‐related adverse events were reported in 43% of patients: the most common were diarrhea (16%), rash (7%), and fatigue (6%). There were 16 deaths; none were considered treatment related. One patient (1%) had a partial response; 46% had stable disease. Most of the tumor samples analyzed had activating epidermal growth factor receptor gene ( EGFR ) mutations (18 of 20 [90%]); 50% (10 of 20) had a concurrent resistance mutation. Only one sample showed MMNG HOS Transforming gene ( MET ) amplification (the patient had progressive disease), whereas 59% (13 of 22) and 47% (14 of 30) had high levels of expression of epidermal growth factor receptor and mesenchymal‐epithelial transition factor on the basis of H‐scores, respectively. There was no apparent association between biomarker expression and antitumor activity. Conclusion: : The combination of dacomitinib and crizotinib showed limited antitumor activity in patients with advanced non–small cell lung cancer and was associated with substantial toxicity.